Congenital diverticular disease of jejunum presenting as obstruction in adulthood: A case report from Ladakh - Deskit, Padma; Badwal, Maneesha; Dolma, Yangchan (Indian Journal of Case Reports, 2020)
Of the many causes of small bowel obstruction, volvulus of the midgut is seen mainly in paediatric age group only, along with malrotation of the gut. However, the volvulus of the small gut in an adult is rare. Volvulus of the midgut in adulthood could be due to many reasons like long mesentery, adhesive bands, internal herniation, endometrioses, etc. But volvulus occurring due to diverticulosis of small intestine is a rare occurrence. The diverticulosis in most of the adult patient are acquired (pulsion diverticuli) with a diverticular wall having only two layers of the intestine. Congenital diverticulosis with the diverticuli bearing all the layers of the intestine leading to the volvulus of the midgut makes it still rarer. We present the case of midgut volvulus arising due to congenital true jejunal diverticulosis in a 50-years-old adult along with a brief review of the literature. In our case report, volvulus occurred in an adult due to congenital diverticulosis of jejunum making it a difficult preoperative diagnosis and a rare case reporting.